Deteksi Jumlah Bakteri Total dan Coliform pada Sludge dari Proses Pembentukan Biogas Campuran Feses Sapi Potong dan Feses Kuda - Benito, Tubagus; Hidayati, Yuli Astuti; Rusdi, Udju D; Marlina, Eulis Tanti (Fakultas Peternakan Universitas Jambi, 2010)
This study aims to determine the amount of total and coliform bacteria in sludge from the process of forming a mixture of biogas feces of beef cattle and horse feces. The method used in this study is the experimental method in the laboratory using a completely randomized design with 3 treatments, ie P1 = C / N ratio of 25, P2 = C / N ratio of 30 and P3 = C / N ratio of 35 and replications 6 times. To determine the effect of treatments, data were analyzed with ANOVA and Duncan test. The results showed that the mixture of feces of beef cattle and horse feces with various C / N ratio had significant ffect on total bacteria and coliform in sludge. Treatment P3 (C / N ratio 35) to produce the total number of bacteria (4.95 x 107 cfu / g) and coliform (6.33 x 106 cfu / g) the lowest.